Role of dermatoglyphics as an indicator of precancerous and cancerous lesions of the oral cavity - Ambika Gupta; Freny R Karjodkar (Wolters Kluwer Medknow Publications, 2013)
Background: Oral squamous cell carcinoma (SCC) is one name that causes panic and holds an undeserved high ranking as a killer. Another important condition which has become a major public health issue in South East Asia is oral submucous fibrosis (OSF). Not all the people using tobacco suffer from these diseases. Genetic predisposition might explain such an individual variability that can be predicted by using various cytogenetic markers. However, these studies are far more costly and complicated. So, dermatoglyphics may be of immense clinical significance to segregate those individuals who are at an increased risk for developing these diseases. Aim: The present study was conducted to analyze the palmar dermatoglyphics in SCC and OSF and find a "dermatoglyphic marker", if any. Study Design: Cross sectional study. Materials and Methods: 120 individuals were divided into four groups based upon their habits of tobacco/areca nut usage and presence of OSF/SCC. Dermatoglyphic patterns were recorded using standard ink method. Various patterns were analysed statistically in the four groups. Results and Conclusion: In SCC, there was an increase in frequency of arch and ulnar loop patterns on fingertips, decrease in frequency of simple whorl patterns on fingertips, decrease in frequency of palmar accessory triradii on right and left hands. Significant findings in OSF included an increase in frequency of arch and ulnar loop pattern, decrease in frequency of simple whorl patterns on fingertips, decrease in atd angle on right hand, decrease in frequency of palmar accessory triradii on right hand. The results revealed that the field of dermatoglyphics holds promising results for determining the genetic susceptibility of individuals to develop SCC and OSF.